John and the Synoptic Gospels. What John Knew and What John Used - Mihăilă Corin (Perichoresis: The Theological Journal of Emanuel University, 2024)
The relationship of John’s Gospel to the Synoptics Gospels is difficult to explain. That is the reason why there have been many proposals, even from the beginning of the church. Not even today, scholars have reached consensus. Rather, there are many competing explanations. Yet, they can be grouped into three categories, according to what John knew and what he used in writing his gospel: (1) John did not know the Synoptics; (2) John knew the Synoptics and used them as literary sources; and (3) John knew the Synoptics but did not use them. Of these three categories, the third one best explains the similarities and the differences between John and the Synoptics. But beyond stating that John knew the Synoptics but did not use them as literary sources, one is on a rather uncertain territory. Therefore, it is historically and literarily plausible to see John as being aware of the Synoptics and even having read them, but whether he chose to harmonize them, adapt them, supplement them, or reinterpret them, is less clear. In the end, it is clear that John wrote a different Gospel, yet it should be read alongside and not instead of the Synoptics.